Identities and Organisations. Evaluating the Personality Traits of Clients in Two Danish Rehabilitation Organizations - Mik-Meyer, Nanna (Outlines. Critical Practice Studies, 2006)
This article explores how the guidelines for personality assessments in two Danish rehabilitation organizations influence the actual evaluation of clients. The analysis shows how staff members produce institutional identities corresponding to organizational categories, which very often have little or no relevance for the clients evaluated. The goal of the article is to demonstrate how the institutional complex that frames the work of the organizations produces the client types pertaining to that organization. The rehabilitation organizations’ local history, legislation, along with the structural features of the labour market and social work result in a number of contradictions that make it difficult to deliver client-centred care. According to the staff, this is one of the most important aims of “good” social work.